An AC-DC topology based on an interleaved modular multilevel converter feasible to solid-state transformer applications - Joca, Davi Rabelo (2019)
This work aims to present the theoretical study, the numerical analysis and the experimental validation of a power electronics converter topology based on an interleaved modular multilevel converter with medium-frequency transformer. The architecture is suitable for the AC-DC stage in solid-state transformer applications for the connection between a medium-voltage AC grid and a low-voltage DC grid. The interleaving reduces the switch conduction losses. The 10 kHz medium-frequency transformer provides galvanic isolation and connects the interleaved modular multilevel converter to a full-bridge converter. From the converter structure, the principle of operation, the modeling, the modulation technique, and the control scheme are discussed. One feature of the converter is the simultaneous generation of the low-frequency grid voltage and the medium-frequency transformer primary voltage. The capacitor voltage balancing and the circulating currents minimization are combined together in a single algorithm. The control system regulates the AC current and the DC bus voltage, on the high-voltage side, and the DC voltage and power flow, on the low voltage side. The experimental validation of the converter is made with a scaled-down single-phase 720 W prototype. The results demonstrate the control system stability in steady-state and dynamic (load step, power flow inversion) operations.